Deleterious Results of Safety Seeking Behaviours in Panic Disorder: Polydipsia and Diabetes Mellitus Type 2 - YORGUNER, NEŞE; TOPÇUOĞLU, VOLKAN (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2016)
Panic disorder is an anxiety disorder that involves recurrent panic attacks, which emerge when a harmless stimulus is interpreted as catastrophic. In an attempt to avoid the panic attack or prevent confrontation, the patient exhibits a dysfunctional attitude and behavior, such as evasion and safety-seeking behavior (SSB). Dysfunctional behavior leads to an increase in the recurrence of panic attacks and affects the patient's life in a negative way. According to the cognitive behavioral therapy model, SSB contributes to the continuation of unrealistic beliefs (e.g. physical experiences) regarding and prevents the patient from grasping new information that may potentially contradict the unrealistic cognitions. In this paper, we present a case with a primary diagnosis of panic disorder. Interestingly, this patient developed diabetes mellitus (DM) type 2 and psychogenic polydipsia (PPD) as a consequence of his SSB. PPD is a common occurrence in patients with psychiatric disorders, especially in schizophrenia. Up to now, no case of a panic disorder with either DM or PPD has been reported in the literature. While it is accepted that major depression poses a risk for DM type 2, panic disorder may also increase this risk. Treatment of the panic disorder with cognitive behavioral therapy (CBT) resulted in improvement of PPD and DM type 2. In conclusion, the role of SSB in medical disorders accompanied by psychiatric disorders should be kept in mind when treating these patients.
Keywords: Panic disorder; psychogenic polydipsia; type 2 diabetes mellitus; PSYCHOGENIC POLYDIPSIA; WATER-INTOXICATION; ADULTS